Primary otological manifestations of granulomatosis with polyangiitis: a case series. Issue 2 (19th February 2015) - Amiraraghi, N; Robertson, S; Iyer, A
Abstract Objectives: A primary otological presentation of granulomatosis with polyangiitis is rare. We present four cases of granulomatosis with polyangiitis with different otological manifestations. Case report: A literature review of granulomatosis with polyangiitis cases presenting to otolaryngologists was undertaken. A case series review of four patients presenting within a 12-month period was also performed. One patient had serous otitis media which worsened after myringotomy. Two patients presented with acute ear infection and facial palsy and one with acute mastoiditis. All were positive for antineutrophilic cytoplasmic antibody, and three had positive findings upon histological analysis. Conclusion: When acute supposed ear infections fail to respond to treatment (antibiotics or surgery), rarer causes of the symptoms should be considered. By reporting this case series, we aim to improve the early diagnosis of granulomatosis with polyangiitis to enable timely treatment and prevent systemic involvement.